Multiscale Characterizations of Local Properties for Girth Welds of X70 and X80. Issue 7 (17th January 2022) - Cao, Jun; Ma, Weifeng; Zhao, Kang; Wang, Ke; Cai, Ke; Cong, Shen; Ren, Junjie; Nie, Hailiang; Dang, Wei; Liang, Xiaobin; Yao, Tian
Abstract : As pipeline design standards require the parameters of mechanical properties, it is crucial to characterize local properties of grith weld. Consequently, the multiscale characterizations based on indentations are performed to study the local properties of these typical zones: weld metal, heat affected zone (HAZ), fusion zone, and base material. The microhardness is measured for entire girth welds of X70 and X80, and the nanohardness is also obtained to analyze the differences in typical zones of girth welds. Subsequently, the yield strength and ultimate tensile strength in the typical zones of girth welds are characterized by spherical indentation method to analyze the distributions of strength and local hardening capacity. Furthermore, the microstructures of girth welds for X70 and X80 in terms of typical zones are studied to analyze the responses of local properties. Results show that the hardness of cap, filler, and root layers for X70 follows the sequence of cap>filler>root, while that of X80 follows the sequence of filler>cap>root. The softening effect of HAZ is existed in the girth weld of X70. The low hardness and strength in root layer are attributed to polygonal ferrite. Abstract : Multiscale characterizations of local properties for girth welds of X70 and X80 are conducted. The softening effect of heat affected zone (HAZ) is existed in the girth weld of X70. The weld metal (WM) center for X80 is prone to ductile, and the HAZ and fusion zone (FZ) are prone to brittle.